The Relation between Level of Knowledge and Attitude towards Practice of Rabies Disease in Residents in the Area of Puskesmas Kuta II - Sarjana, Ni Kadek Ayu Septiani; Prasetyawati, Arsita Eka; Budiani, Dyah Ratna (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Rabies is a disease of animals (usually vertebrate) which is zoonotic (transmissible to humans). Rabies occurs in 24 out of the 34 provinces of Indonesia. Rabies is caused by a virus in the Family: Rhabdivoridae, Genus: Lyssavirus. Control and vaccination strategies in dogs is deemed to be the most effective and economical method in preventing the incidences of rabies in humans. This study aims to determine whether there is a significant relationship between level of knowledge of and attitude practise employed for rabies in residents of the area covered by Puskesmas Kuta II. Methods: This is a cross-sectional study analysing observations in a sample of people. Sampling was carried out by simple random sampling of 96 residents in the area of Puskesmas Kuta II. In this study, the independent variables are knowledge of and attitudes towards rabies disease while the dependent variable is the practice for rabies. Data for these variables were collected via a questionnaire-based interview. Analyses were then carried out using the chi-square (x2) followed by multivariate analysis using multiple logistic regression, Results: This study showed that knowledge has a significant relationship with practice for rabies disease (p = 0.013; OR 4.240; 95% CI 1.352 up to 13.296). Attitude has a significant positive relationship with the value of practice for rabies disease (p = 0.015; OR 3.073; 95% CI 1.233 up to 7.627). The combined effect of knowledge and attitudes to practice for rabies were approximately 20.90% (Negerkerke R square = 0.209). Conclusions: There was a significant relationship between knowledge and attitudes to practice for rabies disease in residents in the area of Puskesmas Kuta II, the higher level of knowledge and improved attitudes will improve practice for rabies disease amongst residents in the area of Puskesmas Kuta II. Keywords: Rabies, Rabies Prevention, Knowledge, Attitude, Practice